Direct ascorbic acid detection with ferritin immobilized on single-walled carbon nanotubes - C. Dechakiatkrai (2018)
Ferritin protein was noncovalently immobilized onto single-walled carbon nanotubes (SWNTs). This SWNT/ferritin composite was characterized using cyclic voltammetry, UV-visible spectroscopy, Raman spectroscopy, and high-resolution transmission electron microscopy. The use of the SWNT/ferritin film as an amperometric biosensor was demonstrated by sensing 1.0 mM ascorbic acid in phosphate-buffered saline solution with a sensitivity of 767 μAmg. It demonstrated that ferritin protein bound to SWNTs enhances the oxidation reaction of ascorbic acid over 11-fold. © 2007 The Electrochemical Society.